2010
DOI: 10.1017/s0022215110002276
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of middle-ear Silastic sheeting during tympanoplasty: hearing outcomes

Abstract: Patients who had undergone Silastic sheet insertion showed significantly better air conduction, bone conduction and air-bone gap averages one year post-operatively, compared with those who had not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…On examining the full texts, 92 articles were assessed as unsuitable where COM was not the primary disease (7), tympanoplasty subtypes were not the primary intervention (11), the article was not published in English (5), the article did not contain long‐term hearing outcomes (68) or the presented data were too limited (1). Thirty‐nine studies 14‐52 reporting long‐term hearing outcomes and/or complications following middle ear interventions were included for synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On examining the full texts, 92 articles were assessed as unsuitable where COM was not the primary disease (7), tympanoplasty subtypes were not the primary intervention (11), the article was not published in English (5), the article did not contain long‐term hearing outcomes (68) or the presented data were too limited (1). Thirty‐nine studies 14‐52 reporting long‐term hearing outcomes and/or complications following middle ear interventions were included for synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…10 of these studies 20,21,24,25,32,38,39,42,45,52 reported air‐bone gap (ABG) data in sufficient detail so that it could be categorized in to bins of ≤20 dB HL or ˃20 dB HL. Additionally, 14 publications 15,18,19,23,24,35,36,38,42,43,46‐48,52 reported mean pre‐ and post‐operative ABG for patients with and without cholesteatoma in sufficient detail to permit weighted averages for these subgroups to be calculated. Eight studies 18,21,24,32,34,42,45,52 also reported these data for patients that underwent ossicular reconstruction, permitting the calculation of weighted averages for this subgroup.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, cases that needed to correct atelectatic membranes or intraoperative verification of adhesions inside the middle ear were managed by placing a silastic sheet in the medial wall of the middle ear. This stimulates the regeneration of the middle ear mucosa and prevents the formation of adhesions (Ng & Linthicum, 1992;Elmorsy & Amer, 2011;Sanna et al, 2012). In an aerated middle ear, silastic promotes a mucosal lined cavity, without foreign-body reaction, rejection, or chronic inflammatory response (Ng & Linthicum, 1992).…”
Section: Surgical Techniquementioning
confidence: 99%